Middle class, media and modi :making of a new electoral politics - Prabhu, Nagesh (New Delhi Sage, 2020)
"The spectacular victory of Narendra Modi and the BJP in 2014 and again in 2019 demands a nuanced exploration of the factors that led to it. Though the role of the middle class and the media in the making of what is called the 'Modi Wave' is often talked about, a clear-eyed and unbiased look at how they transformed the political landscape in post-liberalization India is still wanting. This book studies how the Indian middle class, once seen as politically indifferent, has gradually become a player of importance. This change, which slowly began in the 1990s, has now reached a crescendo, and Modi has become the icon of the changing economic demands of the middle class and their ideological rightward shift. The new middle class played a decisive role in the electoral outcomes of 2014 and 2019-two elections that have undoubtedly changed the way India imagines itself and how the rest of the world sees India. Modi's management of mainstream and social media-primary consumers of which is the ever-growing middle class-has played a key role in his emphatic victories. This book will help the reader understand the arsenal that Modi used in these elections and is a must-read for scholars of politics, media studies and sociology. Nagesh Prabhu is Deputy Editor, The Hindu, Bengaluru, and the author of Reflective Shadows: Political Economy of World Bank Lending to India (2017)"--
Keywords: Politics and government; Middle class--Political activity